A comparison of sexual behaviour and attitudes of healthy adolescents in a Danish high school in 1982, 1996, and 2001 - McGarrigle Christine A; Andersen Berit; Kangas Ida; Østergaard Lars (BMC, 2004)
Abstract Aim To assess changes in sexual behaviour among students at a high school in Denmark from 1982 to 2001. Methods An anonymous self-administered questionnaire was used to compare data from three identical cross-sectional surveys performed in 1982, 1996, and 2001. Results Girls: More girls reported their first sexual intercourse before their 16th birthday in 2001 (42%) than in 1996 (29%) In 1982 it was also 42% (Chi-square for trend: p = 0.003). Fewer girls with no regular partner used condoms for their personal protection in 2001 (2%) than in 1996 (9%) and 1982 (0%) (Chi-square for trend p = 0.016). The proportion of girls with no regular partner who considered protection from sexually transmitted disease important for their choice of contraception was 39% in 2001 compared with 71% in 1996 and only 10% in 1982 (Chi-square for trend: p < 0.0001). Boys: More boys reported sexual debut before their 16th birthday in 2001 (40%) than in 1996 (37%) and 1982 (24%) (Chi-square for trend: p = 0.023). For boys with no regular partner, condom was preferred for personal protection by 85% in 2001, 91% in 1996 and 61% in 1982 (Chi-square for trend p = 0.007). Protection against sexually transmitted infection declined, especially among boys with no regular partner, from 51% in 2001 to 72% in 1996 and 21% in 1982 Chi-square for trend: p < 0.0001). The tendency towards earlier sexual debut and less use of safe sex practices to protect against sexually transmitted infections (STI) was accompanied by a rise in the number of detected STIs during this period. Conclusions The period from 1982 to 1996 during which sexual attitudes were directed toward safer sex seems to have given way to a reverse trend in the period from 1996 to 2001. These findings may have significant implications for health care authorities organising preventive strategies for healthy adolescents.